On the error and outage performance of coherent UWB systems over indoor wireless channels - Abou-Rjeily, Chadi (2017)
In this paper, we propose an accurate method for evaluating the performance of Ultra-Wideband (UWB) coherent receivers over the IEEE 802.15.3a channel model. Depending on the severeness of fading, the method consists of approximating the distribution of the captured channel energy by either a Coxian, gamma-mixture or lognormal distribution based on a least square fitting criterion. The proposed approximations lend themselves to simple mathematical analysis and turn out to be useful in evaluating the performance, in terms of average bit-error-rate (BER) and outage probability, over the IEEE 802.15.3a channels.